WISANGGENI: SANG PENGGUGAT EKSISTENSI DIRI - Dewi, Nenden Rikma (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2012)
Wisanggeni: Sang Penggugat Eksistensi Diri. This research discusses Seno Gumira Ajidarma's reception on Mahabharata's version of Wisanggeni entitled Wisanggeni: Sang Buron. The interpretation of his reception is discussed using literature reception approach and interpreted with Existentialism theory. Theoretically, Heideger stated that existentialism is based on the existence of human beings as individual related to the environment, both physically and mentally. This leads to identify how a person make a journey to search his existence. Conducting the research, the method used is analytic descriptive. The data are described and analyzed objectively from both works. The resultshows that men always make a journey, both physically and mentally, to find their lives’ purpose and how to deal with it.